The Literary Image in Writings and Practical Well - Being in Reality: The Psychological Exploration of Female Migrant Workers in China - Huang, Yuwei; Liang, Xiaohui (Journal of Theory and Practice of Social Science, 2024)
Background: the core of literary works is to reveal the epitomizing image in society so as to provoke the bottom of people’s heart. The image of female migrant workers is always touching the nerve of public since this vulnerable group keeps suffering from class, gender and so on. In 2022, the number of rural migrant workers in China had surged to 295.62 million, 36.6 percent were female which rose by 0.7% from the previous year. The psychological health of this huge group still lagged behind though the living condition and other welfare are improve compared with that in the past. The solution remain unanswered and the landscape of their psychological health needs further delve into. Method: the study explores the psychological dynamics from three different angles such as mental emancipation, consumer behavior and “technology transformation” enlightened by epitomizing image of female migrant workers in literary writings. There are 1574 female migrant workers, who have been divided in three groups depends on their age (660 - group 1; 584 - group 2; 330 - group 3), have participated in the questionnaire and the data has been analyzed by SPSS so as to further study the connotation and enlighten us to figure out strategies to better help their psychological health with different age groups. Results and Conclusion: The findings highlighted the different psychological problems and features in different age groups, the younger generation (< 30) is living more freely and does not take “traditional burden” as the imperatives; however, they still find themselves stuck in class transition. To middle age group (30-45) and senior age group (> 45), data indicates their heavy burden and suffer from the technology advancement etc. Unlike male migrant workers, the female group is more vulnerable due to several unique factors such as low social status which renders us to find better solution to help via the clear unique features as the study unearthed.